Dare to jump : everything you want is on the other side of fear - Dumont, Cedric, ....- (Leuven : LannooCampus, 2020)
Dare to Jump helps you overcome your fear and offers three power skills in becoming the best version of yourself: a limitless mindset, a laser focus and creating trust. It teaches you why focus is the new IQ, how you can train yourself to get into a state of flow, and how to build trust without limits within your team.
Keywords: Leidinggeven; Zelfontplooiing